BlueStar Office Supply Company. Issue 1 (1st November 2018) - Thomas, Rodney; Rutner, Stephen; Boone, Christopher
Abstract : This case study addresses a number of common transportation management issues. It provides an opportunity to analyse historical freight payment data in order to reduce transportation costs and improve customer service, allowing students to utilise real freight payment data and order shipment history data to make recommendations that have strategic implications for both cost and service performance.